Landslide assessment using Normalized Difference Vegetation Index (NDVI) technique in Sentong, Lojing, Kelantan, Malaysia - Chong Kah Min; Arham Muchtar Achmad Bahar; Wani Sofia Udin (Universiti Malaysia Kelantan, 2016)
The study area is a part of Lojing and it is lies between latitude 4° 45’ 30” N – 4° 49’ 0” N and longitude 101° 45’ 30” E – 101° 48’ 30”E. This study was focused on assessing of vulnerable locations of landslide based on satellite imageries of different years (2006, 2014 and 2015) which selected for visual interpretation and vegetation indices (VIs). As a result, there were 18 locations of landslide determined which landslide had occurred. With the aid of historical satellite imagery and the obtained quantitative data, the areas for landslide occurred were detected. Besides, the approach of remote sensing technique in landslide assessment was defined in terms of the early precautions for landslides, thus, the lost from landsides can be reduced. Furthermore, the condition of existing landslide areas was monitored by referring to the satellite imagery. This study can helpful to develop the inhabitant of the area and as well as to improve the poverty eradication.